THE INFLUENCE OF SERVICE QUALITY AND TAX SANCTIONS TO THE OBEDIENCE OF INDIVIDUAL TAXPAYER (CASE STUDY OF INDIVIDUAL TAXPAYER IN TAX OFFICE SOREANG 2016) - Purwanto; Hasna Safira (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2018)
This study is to find out the influence of service quality and tax sanctions to the obedience of individual taxpayer with case study in Tax Office Soreang, using descriptive and verificative method with 150 respondents as taxpayers. This study uses Pearson Product Moment Correlation and multiple regression analysis. The result of analysis showed that the service quality variable with correlation coefficient is 0.740 while the tax sanction with the correlation coefficient is 0.672, both are categorized as a strong correlation. The study is still relatively rarely done, especially in Tax Office Soreang, so it is expected to contribute to find solutions so that the obedience of individual taxpayer can increase